Improving the anti-thermal-shock properties of Sc2O3-Y2O3-ZrO2-CaF2-PHB abradable coatings by fabricating the textures on ceramic matrix composites: experiment verification and numerical analysis - Jing, Jian-nong; Zhang, Le; Li, Qi-lian; Wang, Chun; Dong, Li-hong; Wang, Hai-dou; Lin, En (Frontiers in Materials, 2023)
The abradable coating is one of the most important coatings for improving the efficiency of aeroengine. To improve the durability of Sc2O3-Y2O3-ZrO2-CaF2-PHB abradable coating under the conditions of high temperature thermal shock, the femtosecond laser processing technology is proposed to fabricate the texture on the surface of SiCf/SiC composites to improve the coating/matrix contact area. The environmental barrier coating (EBC) was prepared by vacuum plasma spraying (VPS) equipment on SiCf/SiC ceramic matrix composites to avoid water-oxygen corrosion.And the abradable coating was prepared by air plasma spraying (APS) equipment on the EBC. The thermal shock test of the abradable coating at (1250 ± 50) ℃ was established in the simulated gas environment of the oxygen-propane flame, and the variation of interface stress between the layers during the thermal shock test was analyzed by ANSYS software. The hidden crack between the layers was detected by an infrared thermal imager. The results show that the surface textures have significant influences on the anti-thermal-shock properties of Sc2O3-Y2O3-ZrO2-CaF2-PHB abradable coating by improving the contact area and optimizing the interface stress distribution. The bonding strengths of the coating are increased by 14.6% and 42.2% when the surface textures increase the contact area of the substrate and the coating by 41.3% and 104%, respectively. Compared with the coatings without texture treatments, the coatings with texture treatments can reduce coating thickness by 30% and the coatings do not peel off after the thermal shock tests. Influenced by the cyclic thermal stress, the cracks of abradable coating are initiated at the defect position and gradually propagated a shell-like shape. The textures on the surface of SiCf/SiC composites have deep influences on improving the high-temperature thermal shock life of Sc2O3-Y2O3-ZrO2-CaF2-PHB abradable coating.